Peningkatan Peran “Konsiliasi” dalam Alternatif Penyelesaian Sengketa di Indonesia - Wagiman Wagiman; Sukh Pawen Jit Kaur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Conciliation is one form of Alternative Dispute Resolution (ADR) that holds great potential for resolving disputes efficiently, participatively, and peacefully outside the courtroom. However, in the Indonesian legal practice, the role of conciliation remains limited and is less popular compared to mediation and arbitration. The main obstacles hindering the development of this mechanism include low public and legal practitioners' awareness, the absence of adequate technical regulations, and the lack of professional conciliation institutions. In fact, conciliation aligns well with Indonesia's legal culture that emphasizes deliberation and consensus. The purpose of this article is to examine the effectiveness of the legal framework for conciliation in Indonesia, identify the barriers to its implementation, and formulate strategies to strengthen conciliation within the national legal system. This study employs a normative juridical method with a statutory and doctrinal approach, complemented by analysis of applicable legislation and legal literature. The findings reveal that conciliation lacks a strong and operational legal framework. The absence of procedural standards, supervisory mechanisms, and training systems for conciliators hampers its effectiveness. On the other hand, conciliation has great potential to reduce the burden on courts, expedite dispute resolution, and preserve good relationships between parties. The article concludes that a comprehensive legal reform is urgently needed, including specific regulations, the establishment of independent conciliation institutions, and public education, so that conciliation can play a strategic role in the national dispute resolution system.